Effect of Heat Treatment on Joint Properties of Laser-Welded Ag-Au-Cu-Pd and Co-Cr Alloys - Ikuya Watanabe, DDS, PhD;1 Andrew P. Benson, BS;2 and Khoi Nguyen, BS2 (Journal of Prosthodontics, 2005)
This study investigated the effect of heat treatment on the strengths of laser-welded cast Ag-Au-Cu-Pd and Co-Cr alloys.